Structural Inequities and Barriers to Accessing Kidney Healthcare Services in the United States: A Focus on Uninsured and Undocumented Children and Young Adults - Iorember, Franca M.; Bamgbola, Oluwatoyin F. (Frontiers in Pediatrics, 2022)
The population of children living in poverty and lacking healthcare insurance has increased in the United States of America in the last decade. Several factors have been responsible for this trend including illegal immigration, socioeconomic deprivation, young age, racial segregation, environmental degradation, and discriminatory housing policies. These systemic barriers have contributed to the exclusion of families from essential healthcare services. They are also contributory to the development of chronic illnesses (such as dialysis-dependent kidney disease) that are debilitating and frequently require considerable therapeutic resources. This unfortunate scenario creates a never-ending vicious cycle of poverty and diseases in a segment of society. For pediatric nephrologists, the challenges of caring for uninsured children with chronic kidney disease are all too familiar. Federally funded healthcare programs do not cover this patient population, leaving them the option of seeking care in emergency healthcare settings. Presentation with a critical illness often necessitates urgent placement of vascular catheters and the choice of acute hemodialysis. Adverse social environment influences the need for protracted chronic hemodialysis and a delay in kidney transplantation. Consequently, there is greater comorbidity, recurrent hospitalization, and a higher mortality rate. New policies should address the deficit in health insurance coverage while promoting social programs that will remove structural barriers to health care resources for undocumented children and young adults.